Pengaruh Purifikasi Terhadap Kandungan Zat Aktif dan Aktivitas Antioksidan Ekstrak Etanol 50% Daun Kelor (Moringa oleifera L.) - Diyan Sakti Purwanto; Hari Susanti; Nining Sugihartini (Jurnal Farmasi Indonesia, 2021)
Purification extract ethanol 50% of Moringa dry leaves was carried out to increase the active substance content of flavonoids, β-carotene, saponins and tannins which have antioxidant activity. The purpose of this study was to determine the optimal solvent between ethyl acetate and n-hexane in the ethanol extract fractionation of 50% Moringa leaves. The viscous extract obtained was then purified by fractionation. Fractionation was carried out by dissolving the viscous ethanol extract of 50% Moringa leaves (E1) in aquadest of 70ºC and then adding ethyl acetate to a separating funnel to obtain ethyl acetate (E2) fraction. In addition, the viscous ethanol extract of 50 % Moringa leaves (E1) was fractured with n-hexane (E3). The extract and fraction were evaluated for the parameters including the water level of the extract with gravimetry, levels the β-carotene by HPLC and the antioxidant activity with DPPH . Data were analyzed statistically with a confidence level of 95%. The results the water level of the ethanol extract of 50% Moringa leaves is 4.16 with a CV of 4.62%. The β-carotene level on fractured with n-hexane (E3) then ethyl acetate fraction (E2) and ethanol extract 50 % (E1) that is 1.48 ± 0.01%, 1.19 ± 005% and 0.73 ± 0.01%. While antioxidant activity (IC50) were the most optimal in the n-hexane fraction(E3) then ethanol extract 50 % (E1) and ethyl acetate fraction (E2) that is 40.83 ± 0.04 ug/ml, 47.75 ± 0.09 ug/ml and 58.79 ± 0.10ug/ml. The ethanol extract of 50% Moringa leaves and n-hexane fraction were included in the very strong category while the ethyl acetate fraction was included in the strong category so that it has the potential to be an antioxidant.